2019
DOI: 10.1039/c9cc04364k
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic interface and compositional engineering of inverted perovskite solar cells enables highly efficient and stable photovoltaic devices

Abstract: Interface engineering by PFN-P2 and compositional engineering using water additive enable an efficient and stable perovskite solar cell with 20.5% efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…As one of the most competitive materials in the photovoltaic field, organic-inorganic hybrid halide lead perovskites (ABX 3 , where A is a monovalent cation, B is a divalent cation and X is a halide ion) have attracted great attention in recent years [1][2][3][4]. Through structural engineering [5,6], surface interface engineering [7,8], solvent engineering [9,10] and incident light management engineering [11,12], current organic-inorganic hybrid perovskite-based photovoltaic devices have demonstrated power conversion efficiencies (PCEs) of over 25.2% [13]. They show broad application prospects in the new generation of the green energy industry.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most competitive materials in the photovoltaic field, organic-inorganic hybrid halide lead perovskites (ABX 3 , where A is a monovalent cation, B is a divalent cation and X is a halide ion) have attracted great attention in recent years [1][2][3][4]. Through structural engineering [5,6], surface interface engineering [7,8], solvent engineering [9,10] and incident light management engineering [11,12], current organic-inorganic hybrid perovskite-based photovoltaic devices have demonstrated power conversion efficiencies (PCEs) of over 25.2% [13]. They show broad application prospects in the new generation of the green energy industry.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, NiO is an inorganic HTL, showing good potential for the fabrication of high‐efficiency devices. [ 39,40 ] There are also many organic HTLs recently developed for efficient and stable PSCs, [ 41,42 ] but only small‐molecule HTLs show great potential to evaporate thermally without any decomposition. [ 43 ] For instance, Hsiao et al [ 44 ] used 4,4′‐cyclohexylidenebis[ N,N ‐bis(4‐methylphenyl)benzenamine](TAPC) as a HTL with evaporation potential and reported all vacuum‐processed PSCs with a PCE of up to 17.6%.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the most commonly used oxides include TiO 2 [2,15], ZnO [16] although a variety of other metal oxides [17,18], such as Nb 2 O 5 [19] and SnO 2 [20,21], may also be used, allowing some control of the interfacial properties and variability in junctions formed between electrodes and the CH 3 NH 3 PbI 3 layer. Recently, reports of new metal oxide-based PSCs have demonstrated that PCEs in the range of 15~20% are possible via development and optimization of new oxide layers [22][23][24][25][26][27][28][29][30]. These inorganic oxides are considered excellent interfacial materials due to their superior stability and electrical properties.…”
Section: Introductionmentioning
confidence: 99%